2019
DOI: 10.1039/c9sc04289j
|View full text |Cite
|
Sign up to set email alerts
|

Merging hypervalent iodine and sulfoximine chemistry: a new electrophilic trifluoromethylation reagent

Abstract: Two prominent trifluoromethylation reagent classes join forces in a bench stable hypervalent iodosulfoximine CF3 transfer agent. We report its synthesis, properties and reactivity, opening up new possibilities in trifluoromethylation chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 63 publications
0
47
1
Order By: Relevance
“…Taking heptane-Scheme2.Substrate scope of trifluoromethylation of aliphaticalcohols with 2.F or all substrates which are oils no heating was required, in cases where the starting material was as olid the reaction was conducted at the melting pointoft he compound if applicable or in solvent. Yields were based on reagent 2 and determined by 19 1,6-diol, we found the reagent to have 56:40 chemoselectivity for primary alcohols vs. secondary,f urther highlighting the good reactivity of 2 with secondary alcohols. The chemoselectivity for primary alcohols over tertiary gave 73:27 selectivity when using 3-(hydroxymethyl)-1-adamantol.…”
Section: Entrymentioning
confidence: 74%
See 3 more Smart Citations
“…Taking heptane-Scheme2.Substrate scope of trifluoromethylation of aliphaticalcohols with 2.F or all substrates which are oils no heating was required, in cases where the starting material was as olid the reaction was conducted at the melting pointoft he compound if applicable or in solvent. Yields were based on reagent 2 and determined by 19 1,6-diol, we found the reagent to have 56:40 chemoselectivity for primary alcohols vs. secondary,f urther highlighting the good reactivity of 2 with secondary alcohols. The chemoselectivity for primary alcohols over tertiary gave 73:27 selectivity when using 3-(hydroxymethyl)-1-adamantol.…”
Section: Entrymentioning
confidence: 74%
“…Based on our previousf indings, [17] we expected the reagents to form a2 :1 reagent•Zna dduct, DFT calculations on the optimized adducts indicated that [ZnNTf 2 (2) 2 ]NTf 2 is thermodynamically favored compared to [ZnNTf 2 (1) 2 ]NTf 2 by 6kcal mol À1 in solution (see Supporting Information for details). To furtherv alidate the predicted stoichiometry, 19 FNMR experiments werec onducted, which showed ad ownfield shift of the I-CF 3 signal upon addition of increasing amounts of Zn(NTf 2 ) 2 as ar esult of the increasingi odonium character of 2. [23] Broadened signals were observedu pon addition of up to 0.50 equiv.o ft he zinc catalyst, with sharpeneds ignals observed thereafter suggesting the likelihood of a2:1 adduct.…”
Section: Entrymentioning
confidence: 99%
See 2 more Smart Citations
“…69 However, it is comparable and only marginally shorter than the exocyclic HV I-O bond in the a related heterocylic compound with a hydroxy ligand, I-hydroxybenziodoxolone (2.00 Å), 70 and in the even more closely related benziodazole with methoxy ligands (2.23 Å). 54 More noteworthy is the length of the endocyclic I-N bond (2.37 Å), which was markedly longer than the I-N bonds in a bicyclic benziodazole with two HV I-N bonds (2.18 Å each), 71 I-chlorobenziodoazole (2.11 Å), 72 I-chlorosulfoximine (2.10 Å), I-trifluoromethylsulfoximine (2.28 Å), 73 and I-acetoxybenziodoazole (2.10 Å). 53 At the same time, the I-N bond in BIAT-OH 5 is shorter than I-N bonds with pronounced ionic character, e.g., in I-phenylbenziodazole (2.45), 74 and other compounds with pyridine coordinated to the HV iodine(III) atom (2.41-2.44 Å).…”
Section: Resultsmentioning
confidence: 99%